IMPLEMENTASI MODEL PENDIDIKAN KARAKTER BERBASIS KELUARGA TERINTEGRASI PEMBELAJARAN PAUD DALAM MENANAMKAN SIKAP TOLERANSI PADA ANAK USIA 5-6 TAHUN - Dinah Afifah Yosi (P3M STKIP 'Aisyiyah Riau, 2023)
This study aims to observe the implementation of a family-based character education model in instilling an effective attitude of tolerance in children aged 5-6 years. This research using a qualitative method with a descriptive analysis approach. Data obtained through observation, interviews, and documentation. The results of the study indicate that an effective family-based character education implementation model has been implemented in accordance with the steps that include 4 components, namely: Objectives, Programs, Processes, and Evaluations, which are integrated in learning. There are supporting factors in this implementation, including a positive environment, facilities and infrastructure as well as comfortable and religious school conditions, and the attitude of parents who pay attention to children's development. The inhibiting factors are the different characteristics and abilities of children, and the role of parents who are not supportive.